Early diagnostic markers of sepsis after oesophagectomy (including thromboelastography) - Durila, Miroslav; Bronský, J; Haruštiak, T; Pazdro, Alexander; Pechová, Marta; Cvachovec, Karel (BMC anesthesiology, 2012)
BACKGROUND: Early diagnosis of sepsis and its differentiation from the noninfective SIRS is very important in order that treatment can be initiated in a timely and appropriate way. In this study we investigated standard haematological and biochemical parameters and thromboelastography (TEG) in patients who had undergone surgical resection of the oesophagus to find out if changes in any of these parameters could help in early differentiation between SIRS and sepsis development. METHODS: We enrolled 43 patients (aged 41-74 years) of whom 38 were evaluable. Blood samples were obtained on the morning of surgery and then at 24-hour intervals for the next 6 days. Samples were analysed for procalcitonin (PCT), C-reactive protein (CRP), interleukin-6 (IL- 6), aspartate transaminase (AST), alanine transaminase (ALT) , lactate, white blood count (WBC), D-dimers, antithrombin (AT), international normalised ratio (INR), activated partial thromboplastin time (APTT) and parameters of TEG. RESULTS: Significant differences between patients who developed sepsis during this period (9 patients) and SIRS were found in ALT on Day 1, in AST on Days 1-4, in PCT on Days 2-6; in CRP on Days 3-6; in IL-6 on Days 2-5; in leucocytes on Days 2, 3 and 6; and in D-dimers on Days 2 and 4. Significance values ranged from p < 0.0001 to p < 0.05. CONCLUSIONS: Sequential measurements of ALT, AST, PCT and IL-6 during the early postoperative period can be used for early differentiation of sepsis and postoperative SIRS after oesophagectomy. Among the coagulation parameters measured, only D-dimer concentrations appeared to be helpful in this process. TEG does not seem to be a useful early predictor of sepsis development; however it can be used to differentiate sepsis and SIRS from Day 5 after surgery.